Symptomatic versus asymptomatic COVID-19: does it impact placental vasculopathy?. (12th December 2022) - Ramey-Collier, Khaila; Craig, Amanda M.; Hall, Allison; Weaver, Kristin E.; Wheeler, Sarahn M.; Gilner, Jennifer B.; Swamy, Geeta K.; Hughes, Brenna L.; Dotters-Katz, Sarah K.
Abstract: This study sought to assess the impact of COVID-19 on placental vasculature in the context of maternal symptomatology – comparing asymptomatic to symptomatic pregnant patients – and disease severity – comparing pregnant patients with mild, moderate, severe, and critical COVID-19 infection. PCR-confirmed COVID-19 positive pregnant patients in a single health system who delivered between 3/2020-5/2021 included. All patients had positive COVID test and delivered during the study period. Primary outcome was incidence of any vascular malperfusion on placental pathology. Secondary outcomes were FVM and MVM on placental pathology. Placental pathology compared between symptomatic (sCOVID) and asymptomatic (aCOVID) patients. Secondary analysis of symptomatic patients, comparing placental pathology between mild disease(mCOVID) and worse disease(moderate, severe, or critical-defined by 2020 NIH guidelines) (dCOVID), also performed. Of 112 patients, 53 (47%) had symptoms. Twenty-seven (24.1%) patients had evidence of vascular malperfusion; 26 (23.2%) had MVM. When comparing aCOVID and sCOVID patients, no difference in rate of vascular malperfusion identified, nor any differences in rates of FVM or MVM. Among sCOVID patients ( n = 53), 39 (74%) had mCOVID and 14 (26%) had dCOVID (moderate n = 4, severe n = 9, critical n = 1). Patients with dCOVID had earlier median delivery GA (37.4wks vs 39.2wks, p = .03). No difference in latency from diagnosis to delivery seen between mCOVID and dCOVID groups (4.4 vs 3.0wks, p = .96). Twelve (30.8%) patients had vascular malperfusion on pathology, all had mCOVID ( p = .02). Eleven (28.2%) mCOVID patients had MVM; no dCOVID patients had evidence of vascular malperfusion ( p = .03). No difference in FVM was found between cohorts. Symptomatic COVID-19 infection did not impact placental vasculature differently than asymptomatic infection, even when stratifying by trimester of infection. Among pregnant patients with symptomatic COVID-19, mild disease was associated with placental vascular changes on the maternal side while severe disease was not. Further studies are needed to understand the implications of these findings.